The Effect of Capital Expenditure and Regional Original Income (Pad) on Regional Financial Independence with Economic Growth As a Moderating Variable in Regency/City Governments in North Sumatra Province in 2011-2016 - Karimah Arify (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
This study aims to test the Capital Expenditure and Local Revenue (PAD) on the Regional Financial Independence at the Government of Regency / City in North Sumatra Province Year 2011-2016 simultaneously and partially. In addition, this study also aims to determine whether Economic Growth could moderate Capital Expenditure and Local Revenue (PAD) on the Regional Finance Self-Reliance. This type of research is associative research. This research was conducted in Regency and Municipality Government in North Sumatera Province. Samples in this research were 18 regencies / cities in North Sumatra Province period 2011- 2016. Technique Data analysis using Multiple Linear Regression Analysis and Moderating Test. The results showed that: 1. Belanja Capital has a negative and significant effect on the Regional Financial Independence, 2. Local Revenue has a positive and significant impact on the Regional Financial Independence, 3. Result result simultaneously shows that the Capital Expenditure and Revenue Original have a significant effect on Independence Regional Finance, and 4. Economic Growth is a moderating variable between the influence of Capital Expenditure and Local Own Revenue on Regional Financial Independence.